Algebraische Kurven, die durch Modulfunktionen uniformisiert werden: 7.10. bis 13.10.1973 - Kneser, Martin; Roquette, Peter (Tagungsbericht, 1973)
v. Asch, Utrecht; R. Berndt, Hamburg; E. J. Ditters, Nijmegen; P. Draxl, Bielefeld; Freitag, Mainz; G. Frey, Heidelberg; W. D. Geyer, Erlangen; E. Gottschling, Mainz; G. Harder, Bonn; H. Helling, Bielefeld; Howe, Bonn; Kiehl, Mannheim; M. Knebusch, Saarbrücken; M. Kneser, Göttingen; H. Kraft, Bonn; Legrady, Hamburg; E. Maus, Göttingen; J. Mennicke, Bielefeld; Petrie, Bonn; H. Pfeuffer, Mainz; A. Pfister, Mainz; Recke, Göttingen; F. Schwarz, Saarbrücken; U. Stuhler, Göttingen; S. Suckow, Mainz; R. Vogt, Saarbrücken; K. Wohlfahrt, Heidelberg
Beitr. teilw. dt., teilw. engl., teilw. franz
Keywords: Konferenzschrift